Conversion Of Industrial Wastes Into Marginal Construction Materials - Aneke, Frank Ikechukwu; Awuzie, Bankole (Acta Structilia, 2018)
The circular economy concept (CE) makes a salient contribution towards resource efficiency through product-life extension, redistribution/reuse, remanufacturing, and recycling as well as re-engineering of organizational processes. The construction industry is renowned for its influence on the attainment of society’s sustainable development (SD) aspirations. As such, there is a need for the industry to embrace CE principles. Yet, the uptake of these principles has not been widely reported in the context of developing economies where greenfield construction activities are burgeoning. This observation gives rise to this study. This article reports on the findings of an investigation into the utility of industrial wastes in the production of marginal construction material. To achieve this objective, a thorough geotechnical evaluation of a selection of readily available industrial wastes such as dolomitic waste (DW), silica fume (SF), and river sand (RS) deployed in different ratios according to the mass percentage of the fly ash (FA) waste to produce FA bricks was conducted. Findings suggest that the utilization of these industrial wastes in the production of FA bricks did not only portray some outstanding characteristics but also showed potential to make salient contributions to society’s sustainable aspirations.
Published Article
Keywords: Bricks; Circular economy; Dolomitic waste; Fly ash; South Africa